Perioperative cardiovascular pathophysiology in patients undergoing lung resection surgery: a narrative review. (January 2023) - Shelley, Ben; Glass, Adam; Keast, Thomas; McErlane, James; Hughes, Cara; Lafferty, Brian; Marczin, Nandor; McCall, Philip
Summary: Although thoracic surgery is understood to confer a high risk of postoperative respiratory complications, the substantial haemodynamic challenges posed are less well appreciated. This review highlights the influence of cardiovascular comorbidity on outcome, reviews the complex pathophysiological changes inherent in one-lung ventilation and lung resection, and examines their influence on cardiovascular complications and postoperative functional limitation. There is now good evidence for the presence of right ventricular dysfunction postoperatively, a finding that persists to at least 3 months. This dysfunction results from increased right ventricular afterload occurring both intraoperatively and persisting postoperatively. Although many patients adapt well, those with reduced right ventricular contractile reserve and reduced pulmonary vascular flow reserve might struggle. Postoperative right ventricular dysfunction has been implicated in the aetiology of postoperative atrial fibrillation and perioperative myocardial injury, both common cardiovascular complications which are increasingly being appreciated to have impact long into the postoperative period. In response to the physiological demands of critical illness or exercise, contractile reserve, flow reserve, or both can be overwhelmed resulting in acute decompensation or impaired long-term functional capacity. Aiding adaptation to the unique perioperative physiology seen in patients undergoing thoracic surgery could provide a novel therapeutic avenue to prevent cardiovascular complications and improve long-term functional capacity after surgery.